Coccycua cinerea Vieillot 1817 (Aves, Cuculidae): New bird species for Venezuela - Navarro, Rosauro (2023)
We observed and captured an individual of Coccycua cinerea Vieillot, 1817 in Corozal, Uracoa location, Uracoa municipality, near conflux of Uracoa River and Mánamo spout, in southern Monagas state, adjacent to Orinoco river delta, Venezuela. Diagnostic identification: Bill is ll-dark, short, and curved. Dark iris and suggestive eye ring. Brown tail most dark towards the tips and black at the rear, and ending in white tips, and black bars in the lower part.  This austral migrant bird represents the first and only record for Venezuela and the northernmost to South America.